Posterior Scleritis after Extraocular Horizontal Muscle Transposition Surgery: A Case Report - Osman Bulut Ocak; Asli Inal; Ebru Demet Aygit; Ihsan Yilmaz; Ahmet Demirok; Birsen Gokyigit (Beyoglu Eye Journal, 2017)
A male patient was diagnosed with bilateral congenital third nerve palsy when he presented at the clinic for the first time in 2001 at the age of 22 with the complaints of decreased visual acuity in the right eye, exodeviation, and movement disability in the medial, upper, and inner gaze. The right eye was diagnosed with anterior segment ischemia and stem cell deficiency, which had developed after strabismus surgery. Lateral rectus (LR) augmented recession and conjunctival recession were performed in the left eye of the patient in 2001. The clinical follow-up was completed. The patient presented at the clinic again in 2014. In 2015, the left LR was transposed to the medial rectus region after being divided in 2 with a Y-split. The inferior part was passed under the inferior rectus and inferior oblique muscles, and the superior part was passed under the superior rectus and superior oblique muscles. When the patient described reduced vision on the postoperative first day, fundus examination was performed, followed by fundus fluorescein angiography. Optical coherence tomography findings were assessed and posterior scleritis was diagnosed. Medical treatment was planned and the case was closely monitored. Posterior scleritis had resolved at the fourth month after the operation. At the last visit, it was observed that preoperative visual acuity values and orthophoria in the primary position had been achieved.